Dynamic perfusion and diffusion MRI of cortical spreading depolarization in photothrombotic ischemia - Yu-Chieh Jill Kao; Wenjing Li; Hsin-Yi Lai; Esteban A. Oyarzabal; Weili Lin; Yen-Yu Ian Shih (Neurobiology of Disease, 2014)
Cortical spreading depolarization (CSD) is known to exacerbate ischemic damage, as the number of CSDs correlates with the final infarct volumes and suppressing CSDs improves functional outcomes. To investigate the role of CSD in ischemic damage, we developed a novel rat model of photothrombotic ischemia using a miniature implantable optic fiber that allows lesion induction inside the magnetic resonance imaging (MRI) scanner. We were able to precisely control the location and the size of the ischemic lesion, and continuously monitor dynamic perfusion and diffusion MRI signal changes at high temporal resolution before, during and after the onset of focal ischemia. Our model showed that apparent diffusion coefficient (ADC) and cerebral blood flow (CBF) in the ischemic core dropped immediately after lesion onset by 20 ± 6 and 41 ± 23%, respectively, and continually declined over the next 5 h. Meanwhile, CSDs were observed in all animals (n = 36) and displayed either a transient decrease of ADC by 17 ± 3% or an increase of CBF by 104 ± 15%. All CSDs were initiated from the rim of the ischemic core, propagated outward, and confined to the ipsilesional cortex. Additionally, we demonstrated that by controlling the size of perfusion–diffusion mismatch (which approximates the penumbra) in our model, the number of CSDs correlated with the mismatch area rather than the final infarct volume. This study introduces a novel platform to study CSDs in real-time with high reproducibility using MRI.